Video Assisted Thoracic Surgery for Indeterminate Pulmonary Nodules. Issue 1 (1994) - Albright, Janet L.; MacArthur, Rick I.; Swain, Julie A.; Tran, Alan T.; Little, Alex G.
Abstract : The approach to patients with indeterminate pulmonary nodules is poorly defined. Should every pulmonary nodule be biopsied, is needle biopsy adequate, and other questions are challenges. Video assisted thoracic surgery or thoracoscopy has added a new diagnostic possibility which is evaluated in this paper. Fifty-five patients underwent thoracoscopy for diagnosis of a solitary pulmonary nodule. There were few complications and mortality was zero. A definitive diagnosis was obtained in all patients, although one required a second thoracoscopic wedge resection and 10 required conversion to an open thoracotomy. As discussed in the paper, thoracoscopy provides the opportunity for safely establishing a definitive diagnosis in all patients with solitary nodules and the authors believe will become a standard part of the evaluation of these patients.